Implantation of Stromal Vascular Fraction Progenitors at Bone Fracture Sites: From a Rat Model to a First‐in‐Man Study. (16th September 2016) - Saxer, Franziska; Scherberich, Arnaud; Todorov, Atanas; Studer, Patrick; Miot, Sylvie; Schreiner, Simone; Güven, Sinan; Tchang, Laurent A.H.; Haug, Martin; Heberer, Michael; Schaefer, Dirk J.; Rikli, Daniel; et al.
Abstract : Stromal Vascular Fraction (SVF) cells freshly isolated from adipose tissue include osteogenic‐ and vascular‐progenitors, yet their relevance in bone fracture healing is currently unknown. Here, we investigated whether human SVF cells directly contribute to the repair of experimental fractures in nude rats, and explored the feasibility/safety of their clinical use for augmentation of upper arm fractures in elderly individuals. Human SVF cells were loaded onto ceramic granules within fibrin gel and implanted in critical nude rat femoral fractures after locking‐plate osteosynthesis, with cell‐free grafts as control. After 8 weeks, only SVF‐treated fractures did not fail mechanically and displayed formation of ossicles at the repair site, with vascular and bone structures formed by human cells. The same materials combined with autologous SVF cells were then used to treat low‐energy proximal humeral fractures in 8 patients (64‐84 years old) along with standard open reduction and internal fixation. Graft manufacturing and implantation were compatible with intraoperative settings and led to no adverse reactions, thereby verifying feasibility/safety. Biopsies of the repair tissue after up to 12 months, upon plate revision or removal, demonstrated formation of bone ossicles, structurally disconnected and morphologically distinct from osteoconducted bone, suggesting the osteogenic nature of implanted SVF cells. We demonstrate that SVF cells, without expansion or exogenous priming, can spontaneously form bone tissue and vessel structures within a fracture‐microenvironment. The gained clinical insights into the biological functionality of the grafts, combined with their facile, intra‐operative manufacturing modality, warrant further tests of effectiveness in larger, controlled trials. Stem Cells 2016;34:2956–2966 Abstract : Schematic diagram of the procedure to generate and implant autologous adipose‐derived cells‐based grafts. Human adipose‐derived cells are intraoperatively isolated and loaded onto ceramic granules within fibrin hydrogels and implanted into humeral fractures. This study is performed in patients as well as in femoral fractures in rats and demonstrates both that this approach is feasible and safe and that adipose‐derived cells, without expansion or exogenous priming with morphogens, can form bone tissue and vessel structures within a fracture‐microenvironment.